THE ROLE OF FATHERS IN CHILDREN'S LIVES (American Journal of Research in Humanities and Social Sciences, 2024)
The role of fathers in the lives of children has evolved significantly over the past few decades, influenced by shifting societal norms, gender roles, and family structures. This article provides a comprehensive analysis of the various ways in which fathers contribute to the development and well-being of their children, drawing on recent studies and research. The discussion encompasses the psychological, social, and economic impacts of paternal involvement, as well as the challenges faced by fathers in contemporary society. This article aims to shed light on the importance of fathers in child development and the policies that can support their active participation in family life.